PERAN ETIKA KOMUNIKASI DALAM MEMBANGUN CITRA MEREK YANG BERTANGGUNG JAWAB - Ananda Azzahra Firdausy; Viar Puryani; Putri Adelia Premesty; Arya Putra Wibowo; Nadhif Asyraf Pranata (Jurnal Humanipreneur, 2026)
Abstract. In the current era of globalization, companies often face various demands that require them to build a positive brand image that could be achieved by being socially and environmentally responsible. The primary focus in building a responsible brand image is not merely about the products or services offered by the company, but rather how a company communicates with consumers and the public. This research shows that ethical communication, which takes into account social and environmental values, can increase consumer trust and maintain a good company reputation. In the context of globalization, brand communication conducted by a company must consider cultural differences and social values in other regions to facilitate the communication of messages that need to be conveyed. Integrating local values into the messages can also enhance consumer trust. Research in the field of ethical communication can help companies to develop more effectively in the global market while being socially and environmentally responsible. Keyword: Brand Image, Consumer Trust, Ethical Communication, Globalization & Culture, Sustainable Development